Grazing pressure in sub-Saharan Africa: An historical perspective - Leeuw, P.N. de; Hiernaux, Pierre H.Y.; Mihoso, V.M. (International Rangeland Congress, Inc., 1999)
Grazing and herd management in sub-Saharan Africa is discussed in a broad ecological, agricultural and geopolitical context. A brief historical overview of the Development of the livestock sector is presented, followed by an assessment of feed supplies and livestock densities in major ecological zones. Herd management by farmers and pastoralists to match feed demand to supplies is considered, and future trends and priorities discussed.